Intensification of Microalgae Lipid Extraction Process Scenedesmus Sp. through Integration of Ultrasonic Pretreatment and Freezing in a Soxhlet System - Frank Camilo Ramíres Rodríguez (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aimed to evaluate the effectiveness of ultrasonic and freezing pretreatment strategies in intensifying the Soxhlet extraction process for lipid recovery from Scenedesmus sp., within the framework of chemical engineering separation processes. Methodology: An experimental laboratory design was employed using dried microalgae biomass subjected to three treatment conditions: control (no pretreatment), ultrasonic pretreatment (30 kHz, 30 minutes), and freezing pretreatment (−20°C, 24 hours). Lipid extraction was performed using Soxhlet extraction with n-hexane as the solvent. The extracted lipids were quantified gravimetrically, and all experiments were conducted in triplicate to ensure reproducibility. Main Findings: The results showed that ultrasonic pretreatment significantly enhanced lipid yield (26.78%), followed by freezing pretreatment (23.12%), compared to the control (18.45%). Process intensification efficiency reached 45.14% for ultrasonic treatment and 25.31% for freezing treatment. The findings indicate improved mass transfer and cell disruption, particularly under ultrasonic conditions. Novelty/Originality of this study: This study introduces a process intensification perspective by integrating ultrasonic and freezing pretreatments into a conventional Soxhlet extraction system, highlighting their potential to optimize traditional extraction processes without requiring advanced or high-cost technologies.